RESPON TANAMAN DAHLIA (Dahlia pinnata) PADA BERBAGAI MACAM MEDIA TANAM DAN PUPUK ORGANIK CAIR - Libria Widiastuti (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2019)
Dahlias have a high potential for development in West Sumatra Province. This is based on a number of cities in West Sumatra such as Bukit Tinggi and Agam Regency which have designated themselves as